Dyslexia and Maths. - Kay, Julie (Taylor and Francis, 2012)
This concise text helps the reader to understand why dyslexics find maths difficult and offers practical ideas for supporting them most effectively. It explains which areas of maths dyslexics tend to have particular difficulty with, assesses current teaching philosophies and methods, describes a framework of general learning principles that allow dyslexics to make progress in maths, and outlines a number of specific and effective teaching recommendations. The book helps teachers at primary and secondary levels to better understand the maths performance of dyslexi.